Peran Lemabaga Bantuan Hukum Dalam Sumber Daya Laut Demi Mewujudkan Keadilan Bagi Masyarakat Pesisir Di Kota Surabaya - Syahputra, Alfa Fajreza; Satria, I Gde Sandy (Jaanur Elbarik Indonesia, 2026)
This study examines the role of Legal Aid Institutions (LBH) in supporting marine resource management and promoting justice for coastal communities in Surabaya City, which have a high dependence on marine resources. Legal issues such as coastal area management conflicts, marine pollution, and unequal access to justice remain prevalent. This research employs a socio-juridical method with a descriptive-analytical approach through the study of laws and regulations, field observations, and interviews. The findings indicate that Legal Aid Institutions play an active role in providing legal education, litigation and non-litigation assistance, as well as policy advocacy related to the protection of marine resources and the rights of coastal communities. However, these roles face challenges including limited resources, low legal awareness among communities, and weak stakeholder synergy